Analysis of Microbial Diversity and Dynamics During Bacon Storage Inoculated With Potential Spoilage Bacteria by High-Throughput Sequencing - Li, Xinfu; Xiong, Qiang; Zhou, Hui; Xu, Baocai; Sun, Yun (Frontiers in Microbiology, 2021)
Dynamics, diversity, and succession of microbial community during storage of bacon were investigated in the current study by inoculating specimens with five potential spoilage bacterial groups: Staphylococcus xylosus, Leuconostoc mesenteroides, Carnobacterium maltaromaticum, Leuconostoc gelidum, and Serratia liquefaciens previously isolated, by high-throughput sequencing of the V3–V4 region of 16S rRNA genes. Each bacterial group was represented by several strains. In addition, combinations of the groups were also examined. These bacterial strains were inoculated on irradiated, sterilised, smoked bacon specimens, and changes of microbial growth and physico-chemical properties were monitored within a fixed time period during storage. A total of 367 bacterial genera belonging to 21 phyla were identified. Control samples had the highest microbial diversity and remained relatively stable throughout the storage period. In contrast, bacterial counts in all inoculated specimens increased significantly in the first 15 days; bacterial community diversity decreased over time. Serratia, Carnobacterium, and Leuconostoc were the predominant genera at the end of storage and were considered to be competitive species, potentially inhibiting the growth of other microorganisms. The present study assessed the viability of five isolated strains, explained the spoilage process and provided potential benefit in the form of extended shelf life.